How number and size of text boxes in argument diagrams affect opinions. (October 2018) - van Amelsvoort, Marije; Schilperoord, Joost
Abstract: Argument diagrams are schematic representations of claim-reason complexes, displaying boxes with standpoints and arguments, and lines or arrows to relate these boxes. In four experiments, we investigate the metaphor framing effect by investigating how the perceptual cues size and number of arguments influence evaluations of arguments. In the first experiment, we looked at the effect of size and number of boxes independent of content, using an empty argument diagram. We asked participants to imagine there were arguments in the boxes and decide whether they would choose in favor or against. Participants chose according to hypotheses: the side that had larger boxes, the side that had more boxes, or the side that had both larger and more boxes. In the other experiments, the diagrams contained real standpoints and arguments. Although content was very important in judging arguments, the effect of perceptual cues was still present. We found that mainly the number of arguments influenced decisions, while size painted a more complicated picture. We discuss these results in the light of argumentation and persuasion for learning. Highlights: The metaphor framing effect extends to visual cues in argument diagrams. People interpret argument diagrams both on content and perceptual cues. Number is more important than size for judging argument diagrams. Multimodal argument diagrams have added value over argumentative texts.